SAT-388 Dry Cough as Only Sign of a Parathyroid Adenoma Producer of PTH - Selman-Geara, Antonio (J Endocr Soc, 2020)
BACKGROUND: The parathyroid adenoma producing an excess of PTH is characterized by hypercalcemia, asthenia, physical weakness and renal lithiasis. This clinical case is presented only with a dry (non-productive) cough sign of long duration.CASE: 51-year-old female born in Padre Las Casas, D.R. presenting with chief complain of dry cough for about four years. Clinical findings: (03/13/2019) Height 62”, Weight 142 lbs, Temperature 36.2 Celsius, BP 90/60 mmHg, RR 16 rpm, HR 60 bpm, on her neck no adenopathies or thyroid changes. Occasional coughing. A sonographic evaluation of the neck (04/09/2019) reveals a solid, heterogeneous nodular image of 0.7 cm x 0.5 cm in the left lobe of the Thyroid (Fig. 1) which by FNAB (04/10/2019) showed a benign adenomatoid node with cystic changes (Bethesda II) (Fig. 2). TEST: (03/20/2019) anti-TG 0.10 IU/mL (NV -115), anti-TPO 9.00 IU/mL (NV -34), TG 9.41 (NV -78 ng/mL), TSH 0.34 μIU/mL (VN 0.27-4.20), free T3 2.05 pg/mL (NV 2.04-4.40), total T3 0.74 ng/mL (NV 0.83-2.00), total T4 8.46 μg/dL (NV 5.1-14.1), free T4 1.61 ng/dL (NV 0.93-1.71) Calcium 10.4 mg/dL (NV 8.1-10.4), Phosphorus 2.6 mg/dL (NV 2.5-4.5), PTH-Intact 157 pg/mL (NV 14.5-87.1) Thyroid-Parathyroid scintigraphy (Sestamibi-Technetium 99mTc04: 15 mCi) (04/23/2019) shows lower left Parathyroid Adenoma (Fig. 3). She undergoes surgery (05/23/2019) removing the left thyroid lobe and left inferior parathyroid gland whose pathology shows chronic nodular colloid goiter, with areas of hemorrhage. Parathyroid adenoma of main cells (Fig. 4-5). Post-surgical TEST (06/24/2019) PTH-intact 69.0 pg/mL (NV 14.5-87.1), Calcium 8.6 mg/dL (NV 8.1-10.4), Phosphorus 2.7 mg/dL (NV 2.5-4.5), anti-TG 10.0 IU/mL (NV <115), anti-TPO 9.00 IU/mL (NV <34), TG 8.92 ng/mL (NV <78), total T3 0.68 ng/mL (NV 0.83-2.00), free T3 1.95 pg/mL (NV 2.04-4.40), total T4 6.40 μg/dL (NV 5.1-14.1), free T4 1.02 ng/dL (NV 0.93-1.71). Post-surgical clinical evaluation (06/21/2019) Weight 142 lbs, Temperature 36.5 Celsius, BP 110/70 mmHg, RR 16 rpm, HR 60 bpm. Patient has not shown signs of coughing. Last TESTS (10/20/2019) Calcium 9.40 mg/dL, Phosphorus 3.10 mg/dL, PTH-intact 24.40 pg/mL, TG 11.90 ng/mL, total T4 6.80 μg/dL, free T4 1.23 ng/dL, total T3 0.88 ng/mL, free T3 2.66 pg/mL, anti-TPO 11.14 IU/mL, anti-TG 10 IU/mL. CONCLUSIONS: Lower left (benign) parathyroid adenoma whose clinical manifestations are not common. Dry (non-productive) cough is not known as a manifestation of elevated PTH-intact. Calcium and Phosphorus levels in normal values. In addition, histological alterations of the left thyroid lobe of benign character with few manifestations of hormonal alterations and normal antibodies. It is of crucial clinical importance to observe and document more cases with similar presentation in order to identify the possible causes of cough with an elevated PTH manifestation.